(untitled) (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: The aim of the present research work was to develop asenapine maleate (AM)-loaded solid lipid nanoparticles (AM-SLN) for the enhancement of oral bioavailability of drug and delivery to the brain. Materials and Methods: A 32 factorial design was used for the development and optimization of AM-SLN. Two independent variables, drug:lipid ratio (X1) and number of homogenization cycles (X2), were selected, while particle size and entrapment efficiency were selected as response variables. The optimized batch was evaluated by various in vitro characterizations and in vivo pharmacokinetic and brain distribution studies. Results: The particle size, polydispersity index, entrapment efficiency, and zeta potential of optimized AM-SLN were found to be 113 ± 4 nm, 0.34 ± 0.05, 72.4 ± 1.73%, and −41.4 ± 2.25 mV, respectively. Pharmacokinetic study indicated significantly higher (P < 0.05) peak drug concentration (142.41 ± 8.14 ng/mL), area under the drug concentrationtime curve (1561.81 ± 36.34 h ng/mL), and mean residence time (15.31 ± 3.21 h) of AM-SLN compared to AM-suspension (77.02 ± 5.74 ng/mL, 299.76 ± 39.42 ng/mL, and 2.73 ± 0.16 h, respectively) through oral route. Brain distribution study showed higher drug permeation across the blood–brain barriers and accumulation in the brain. Conclusion: These findings demonstrate that SLNs could be a new promising drug delivery system for oral delivery of AM in the treatment of schizophrenia.